Characterization of new highly selective pyrazolo[4,3-d]pyrimidine inhibitor of CDK7 - Kovalová, Markéta; Havlíček, Libor; Djukic, Stefan; Škerlová, Jana; Peřina, Miroslav; Pospíšil, Tomáš; Řezníčková, Eva; Řezáčová, Pavlína; Jorda, Radek; Kryštof, Vladimír (Biomedicine & pharmacotherapy, 2023)
Targeting cyclin-dependent kinase 7 (CDK7) provides an interesting therapeutic option in cancer therapy because this kinase participates in regulating the cell cycle and transcription. Here, we describe a new trisubstituted pyrazolo[4,3-d]pyrimidine derivative, LGR6768, that inhibits CDK7 in the nanomolar range and displays favourable selectivity across the CDK family. We determined the structure of fully active CDK2/cyclin A2 in complex with LGR6768 at 2.6 Å resolution using X-ray crystallography, revealing conserved interactions within the active site. Structural analysis and comparison with LGR6768 docked to CDK7 provides an explanation of the observed biochemical selectivity, which is linked to a conformational difference in the biphenyl moiety. In cellular experiments, LGR6768 affected regulation of the cell cycle and transcription by inhibiting the phosphorylation of cell cycle CDKs and the carboxy-terminal domain of RNA polymerase II, respectively. LGR6768 limited the proliferation of several leukaemia cell lines, triggered significant changes in protein and mRNA levels related to CDK7 inhibition and induced apoptosis in dose- and time-dependent experiments. Our work supports previous findings and provides further information for the development of selective CDK7 inhibitors.
Keywords: cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Phosphorylation; buněčný cyklus; Protein Kinase Inhibitors; Selectivity; kinasa aktivující cyklin dependentní kinasy; Pyrimidines; Cyclin-dependent kinase 7; Inhibitor; inhibitory proteinkinas; pyrazolo[4,3-d]pyrimidine; pyrimidiny; Cyclin-Dependent Kinase-Activating Kinase; fosforylace; Cell Cycle